Social and Political Life in Ustrushana in The Ancient and Middle Ages (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
It is known that it is not possible to give a complete description of the external and internal political events that took place in Ustrushana in the early Middle Ages, because the information in the ancient written sources that serve as a basis for the research is extremely scarce. Therefore, since the political life of the studied period is a continuation of the events and incidents that occurred in antiquity, there is a need to cover the political processes of this period in detail.